TANGGUNG JAWAB PEMERINTAH KOTA SAMARINDA TERHADAP PENERBITAN IZIN MENDIRIKAN BANGUNAN (IMB) DI TEPI SUNGAI MAHAKAM - Pranata, Rivaldi Dwi Pranata (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractImplementing agencies or officials of the PBL issuance are also in the spotlight because they are directly related to the licensing of the development carried out and its implications for Spatial Planning. This legal writing aims to determine the responsibility of the city government to grant Permits Building Licenses on the banks of the Mahakam river seen from the aspect of the Spatial Planning Act, the legal effort that can be made against the Granting of Permits Building License (PBL) that is not in accordance with the Urban Planning (UP) based on the Spatial Planning Law, and to find out the conception of compensation for the giving of PBL which is canceled because it is not in accordance with the UP.This type of research is a normative legal research with the approach of Act and conceptual. Using primary, secondary and non-legal sources of legal material. then the legal material is processed in a deductive way and then draws it into a more specific conclusion and is arranged systematically.The results of the study that the government is responsible for issuing PBL in violation of spatial layout by providing compensation imposed on the East Kalimantan Provincial Budget as an incentive in the building that has been established long before the rules apply and does not give permission for the extension of the right to use, the right to use the building. Also provide explanation for the cancellation of Permits Building License. Legal efforts that can be done by the community who feel aggrieved on the permit permit PBL is not in accordance with the UP can be done criminally, civil, and administration. Then the conception of compensation for the cancellation of PBL is through the administrative effort by making a complaint to the Administrative Court because the permit issued is the State Administrative Procedure (SAP), on the existence of deviation or non-conformity of the service with the standard of service causing the material loss.